Comparison between potential and effective cornea donors at the Evangelic University Hospital of Curitiba - Torres, Ilana Barrichello; Araujo, Mariana Sponholz; Benites, Manuela Fiorese; Moreira, Hamilton (Brazilian Journal of Transplantation, 2006)
Purposes: To quantify the potential cornea donors at the University Hospital Evangélico of Curitiba, comparing them with real donors and separate them by hospital units where they were attended; to verify their major base causes of death; to evidence the more prevalent criteria for exclusion whenever the donation was not possible. Methods: Retrospective descriptive study, based on handbooks and death certificates of deaths occurred between April and July of 2006 at the University Hospital Evangélico of Curitiba. Criteria for the donation exclusion were researched by analyzing: death cause and base cause of death, among others parameters. Results: 516 handbooks were analyzed. Stillbirth and up to 2 years old newborns and unidentified patients were excluded amounting a sample of 466 patients. 302 (64.8%) were considered potential donors, 164 (35.2%) not donors. Amongst 302 potential donors, only two donations were performed. This amount represents 0.7% of possible donations. The main base cause of death was malignant neoplasia (29.8%). The majority of potential donors died at the Emergency Room (22.2%), followed by the General Intensive Care Unit (10.5%). The identified exclusion criteria were: Septicemia (87.2%), spread active lymphoma (4.3%), leukemia (3.7%), death due to unknown cause (3.0%), active viral encephalopathy (1.2%), and hepatitis C (0.6%). Conclusion: Compared to the potential cornea donors, the actual amount of corneas donation is quite modest. The sector of major prevalence of potential donors was the Emergency Room. The main base cause of death was neoplasia. The major cause for the exclusion of potential donors was septicemia.